2003
DOI: 10.1023/b:plan.0000006944.61384.11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Brassica napus NAC domain transcriptional activators induced in response to biotic and abiotic stress

Abstract: Subtractive expressed sequence tag analysis and screening of cDNA libraries derived from Brassica napus leaves subjected to mechanical wounding, flea beetle feeding or cold temperatures revealed eight genes encoding NAC-domain transcription factors. The genes were found to be differentially regulated in response to biotic and abiotic stresses including wounding, insect feeding, Sclerotinia sclerotiorum infection, cold shock and dehydration. Five BnNAC proteins were orthologous to Arabidopsis thaliana ATAF1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
225
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(236 citation statements)
references
References 32 publications
5
225
1
5
Order By: Relevance
“…Genes in the ATAF subfamily, including StNAC from tomato and ATAF1-2 from Arabidopsis, were induced by pathogen attack and wounding (Collinge and Boller 2001). In Brassica napus, nine members of the NAC (BnNAC) were identified for their differential expression after feeding with flea beetle and treatment of cold temperature (Hegedus et al 2003). In Arabidopsis, Tran et al (2004) and Fujita et al (2004) reported that three NAC genes ANAC019, ANAC055 and ANAC072 were induced by drought, salinity, and/or low temperature, and the transgenic Arabidopsis plants overexpressing these genes showed improved stress tolerance compared to the wild type.…”
mentioning
confidence: 99%
“…Genes in the ATAF subfamily, including StNAC from tomato and ATAF1-2 from Arabidopsis, were induced by pathogen attack and wounding (Collinge and Boller 2001). In Brassica napus, nine members of the NAC (BnNAC) were identified for their differential expression after feeding with flea beetle and treatment of cold temperature (Hegedus et al 2003). In Arabidopsis, Tran et al (2004) and Fujita et al (2004) reported that three NAC genes ANAC019, ANAC055 and ANAC072 were induced by drought, salinity, and/or low temperature, and the transgenic Arabidopsis plants overexpressing these genes showed improved stress tolerance compared to the wild type.…”
mentioning
confidence: 99%
“…NAC domain has been implicated in nuclear localization, DNA binding, and the formation of homodimers or heterodimers with other NAC domain proteins [11-16]. In contrast, the C-terminal regions of NAC proteins are highly divergent [6-9,14], and confer the regulation diversities of transcriptional activation activity [11,13,15-22]. …”
Section: Introductionmentioning
confidence: 99%
“…To cope with this, plants have evolved elaborate mechanisms in perceiving the attack and responding to the signaling to unite the reception of information to the induction of appropriate defense gene expression (Hegedus et al, 2003). Upon stress, gene expression is tightly regulated in a coordinated and timely manner, and the regulation of gene expression is largely governed by specific transcription factors (Wray et al, 2003).…”
Section: Introductionmentioning
confidence: 99%